ENHANCING STUDENTS’ LINGUISTIC COMPETENCE VIA AUTHENTIC TEXTS IN ENGLISH - Teshabayeva Zamiraxon, Teshabayeva Zamiraxon (Журнал иностранных языков и лингвистики, 2021)
Today, there is a rapid increase in education, therefore, knowledge of foreign languages has become one of the main problems in monitoring the development of the global information and digital economy in our country. Therefore, to improve the foreign language, various pedagogical technologies and methods of teaching the language are used. We know that oral and written speech skills are skills that can be achieved with great difficulty. This project analyses the development of oral and written speech using pedagogical technologies and teaching text types. Particular attention is paid to the development of students' communication skills using pedagogical technologies. These technologies help students gain confidence in self-expression. Therefore, the use of these technologies in lessons effectively develops oral and written speech, provides communication and an exciting learning process.